A Comparision on Text-Based and Graphical Browser (International Journal of Engineering and Computer Science, 2014)
In today world there begins a huge competition between the browser to reach the requirements of the people as, there are so many things that a user required as per their need. In this paper we have taken two browsers into consideration that shows the use, fulfillment, differentiation and various techniques that work with two different types of browsers such as “Text-based” and “Graphical-based”. The conclusion is made by considering both the techniques pros and cons as per the basic features provided by both types of browsers. We had research basically considering two browsers i.e. “IE” for graphical based and “LYNX” for text-based.